Assessment of the Economic Impact of the Adopting Drought Tolerant Maize Varieties in Benin - CGIAR Research Program on Maize (2018)
• About 60 % of farm households have adopted DTM varieties in 2018. • TZE Comp 3DT, EV DT 97, STR W; 2000 Syn EEW; Across 97 TZL Comp 1 were the most widely adopted DT varieties. • Adoption of DT varieties significantly increased household food consumption score (HFCS) by about 17.58% and decreased the household food insecurity score (HFIES) by 25.32%.